Case report: Unusual and extremely severe lipoprotein X-mediated hypercholesterolemia in extrahepatic pediatric cholestasis - Rossella Colantuono; Chiara Pavanello; Andrea Pietrobattista; Marta Turri; Paola Francalanci; Marco Spada; Pietro Vajro; Laura Calabresi; Claudia Mandato (Frontiers Media S.A., 2022)
BackgroundLipoprotein X (LpX) - mediated extremely severe hyperlipidemia is a possible feature detectable in children with syndromic paucity of intralobular bile ducts (Alagille syndrome) but rarely in other types of intra- and/or extrahepatic infantile cholestasis.Case presentationHere we report on a previously well 18-month child admitted for cholestatic jaundice and moderate hepatomegaly. Laboratory tests at entry showed conjugated hyperbilirubinemia, elevated values of serum aminotransferases, gamma-glutamyl transpeptidase (GGT) and bile acids (100 folds upper normal values). Extremely severe and ever-increasing hypercholesterolemia (total cholesterol up to 1,730 mg/dl) prompted an extensive search for causes of high GGT and/or hyperlipidemic cholestasis, including an extensive genetic liver panel (negative) and a liver biopsy showing a picture of obstructive cholangitis, biliary fibrosis, and bile duct proliferation with normal MDR3 protein expression. Results of a lipid study showed elevated values of unesterified cholesterol, phospholipids, and borderline/low apolipoprotein B, and low high-density lipoprotein-cholesterol. Chromatographic analysis of plasma lipoproteins fractions isolated by analytical ultracentrifugation revealed the presence of the anomalous lipoprotein (LpX). Magnetic resonance cholangiopancreatography and percutaneous transhepatic cholangiography showed stenosis of the confluence of the bile ducts with dilation of the intrahepatic biliary tract and failure to visualize the extrahepatic biliary tract. Surgery revealed focal fibroinflammatory stenosis of the left and right bile ducts confluence, treated with resection and bilioenteric anastomosis, followed by the rapid disappearance of LpX, paralleling the normalization of serum lipids, bilirubin, and bile acids, with a progressive reduction of hepatobiliary enzymes.ConclusionWe have described a unique case of focal non-neoplastic extrahepatic biliary stenosis of uncertain etiology, presenting with unusual extremely high levels of LpX-mediated hypercholesterolemia, a condition which is frequently mistaken for LDL on routine clinical tests.